1987
DOI: 10.1159/000212872
|View full text |Cite
|
Sign up to set email alerts
|

The Cholinergic System in Aging

Abstract: A morphometric analysis of neuronal loss during normal aging was performed in the nucleus basalis Meynert complex of the basal forebrain (Nbm) (nucleus septi medialis, nucleus of Broca’s diagonal band, nucleus basalis) and the ciliary ganglion, a peripheral cholinergic structure, in patients free of neurological and psychiatric illness. As a basis for morphometric evaluation of the Nbm complex, a three-dimensional reconstruction of this complex structure was made. Neuronal counts in the Nbm complex and the cil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
22
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 18 publications
6
22
0
Order By: Relevance
“…In parallel to our findings in the NBM of monkeys, Bigl et al [25] found the number of cells in human NBM decreased from anterior to posterior re gions, and did not find an age-dependent change in cell number in any of the divisions of the NBM. In a detailed topographic analysis of morphometric changes in the human NBM, De Lacalle et al [22] did not find a relation ship between cell numbers in the anterior division of the NBM and age, although the mean cross-sectional area of NBM neurons in Ch4a was larger with increasing age.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In parallel to our findings in the NBM of monkeys, Bigl et al [25] found the number of cells in human NBM decreased from anterior to posterior re gions, and did not find an age-dependent change in cell number in any of the divisions of the NBM. In a detailed topographic analysis of morphometric changes in the human NBM, De Lacalle et al [22] did not find a relation ship between cell numbers in the anterior division of the NBM and age, although the mean cross-sectional area of NBM neurons in Ch4a was larger with increasing age.…”
Section: Discussionsupporting
confidence: 91%
“…In con cert with our observations in aged monkeys, several stud ies found stability of NBM neuronal numbers in humans with increasing age [25][26][27], However, an almost equal number of other studies in aged humans reported signifi cant decreases in NBM neuronal numbers [10,11,23,24], The reasons for these discrepancies are not clear, but sug gestions [60] that the inconsistencies between studies may be related to the age of subjects that were included in the studies, or the regions of the NBM that were sampled, may not be entirely accurate. For example, three studies [25][26][27] conducted in the anterior or intermediate aspects of the NBM found no cell loss in subjects between the ages of 25 and 90 years, whereas a similar study [10] did find cell loss in the anterior division of the NBM in subjects within this age range.…”
Section: Discussionsupporting
confidence: 80%
“…Pyri dostigmine is an inhibitor of acetylcholines terase and thus it activates the cholinergic pathway leading to a suppression of somato statin release. In normal aging, the synthesis of brain acetylcholine is known to decline [11, 18-21], whereas choline acetyltransferase ac tivity and the density of muscarinic receptors do not change significantly [11][12][13][14], In the light of these observations, our present results may indicate that in elderly men there is a lower cholinergic inhibitory tone in the con trol of hypothalamic somatostatin release. In fact, when unmasked by pyridostigmine, cho linergic neurotransmission appeared to be markedly reduced in elderly subjects.…”
Section: Discussionsupporting
confidence: 50%
“…However, differences between younger and older sub jects in the metabolic clearance rate of the drug are unlikely, because pyridostigmine is readily absorbed from the gastrointestinal tract [7], and all subjects were in good nutri tional condition. Furthermore, studies of brain cholinesterase do not show significant changes in this enzymatic activity in normal aging [11][12][13][14].…”
Section: Discussionmentioning
confidence: 94%
“…Studies in the primate basal forebrain complex have alternately reported a loss of cholinergic neurons (e.g., Stroessner-Johnson et al, 1992) or no change (Bigl et al, 1987;Voytko et al, 1995;Gilmor et al, 1999), but few used stereological methods of quantification or assessed cell number independent of a potential loss of cholinergic phenotype. In one study of note, Smith et al (1999) found that, although a substantial percentage of cholinergic neurons in the aged monkey Ch4i (a neocortically projecting division of the nucleus basalis of Meynert) are no longer immunoreactive for the p75 receptor, overall neuron number fails to differ as a function of age, and NGF treatment successfully rescues the loss of p75-positive phenotype.…”
Section: Discussionmentioning
confidence: 99%